Implementasi Algoritma Boldi-Vigna Codes Untuk Kompresi File Audio Pada Aplikasi Pemutar Audio Berbasis Web - Sukma Hakiki Silitonga; Surya Darma Nasution (KOMIK (Konferensi Nasional Teknologi Informasi dan Komputer), 2022)
Large storage capacities are currently very important because more and more data must be stored, the size of an audio file is sometimes relatively large, because the longer the duration of an audio, the larger the size of the audio file. The size of a file to be stored greatly affects storage space, meaning that if the file size to be stored is large, a large enough storage space is also needed to accommodate the data. The solution to overcome problems like this is to perform data compression techniques. Data compression aims to reduce a file size which can reduce the bit size in each audio file, but does not eliminate the information data in it. By compressing, large data will be reduced in size so as to save storage space. In this study the algorithm used is the boldi-vigna codes algorithm, by using this algorithm, the compression results of each ζ code have different results for each value, so the compression results will be profitable.